An analysis of policy success and failure in formal evaluations of Australia's national mental health strategy (1992-2012) - Francesca C. Grace; Carla S. Meurk; Brian W. Head; Wayne D. Hall; Meredith G. Harris; Harvey A. Whiteford (BMC, 2017)
Abstract Background Heightened fiscal constraints, increases in the chronic disease burden and in consumer expectations are among several factors contributing to the global interest in evidence-informed health policy. The present article builds on previous work that explored how the Australian Federal Government applied five instruments of policy, or policy levers, to implement a series of reforms under the Australian National Mental Health Strategy (NMHS). The present article draws on theoretical insights from political science to analyse the relative successes and failures of these levers, as portrayed in formal government evaluations of the NMHS. Methods Documentary analysis of six evaluation documents corresponding to three National Mental Health Plans was undertaken. Both the content and approach of these government-funded, independently conducted evaluations were appraised. Results An overall improvement was apparent in the development and application of policy levers over time. However, this finding should be interpreted with caution due to variations in evaluation approach according to Plan and policy lever. Tabulated summaries of the success and failure of each policy initiative, ordered by lever type, are provided to establish a resource that could be consulted for future policy-making. Conclusions This analysis highlights the complexities of health service reform and underscores the limitations of narrowly focused empirical approaches. A theoretical framework is provided that could inform the evaluation and targeted selection of appropriate policy levers in mental health.